Antihypertensive mechanisms of intra-renal dopamine. Issue 2 (March 2015) - Zhang, Ming-Zhi; Harris, Raymond C.
<x xml:space="preserve">Abstract</x> Purpose of review This review will highlight recent findings concerning the regulation and signalling of the intrarenal dopaminergic system and the emerging evidence for its importance in blood pressure regulation. Recent findings There is an increasing evidence that the intrarenal dopaminergic system plays an important role in the regulation of blood pressure, and defects in dopamine signalling appear to be involved in the development of hypertension. Recent experimental models have definitively demonstrated that abnormalities in intrarenal dopamine production or receptor signalling can predispose to salt-sensitive hypertension and a dysregulated renin–angiotensin system. There are also new results indicating the importance of dopamine receptor mediated regulation of salt and water homeostasis along the nephron, and new studies indicating the role that the intrarenal dopaminergic system plays to mitigate the production of reactive oxygen species and progression of chronic renal disease. Summary New studies underscore the importance of the intrarenal dopaminergic system in the regulation of renal function and indicate how alterations in dopamine production or signalling may underlie the development of hypertension and kidney injury.